Less Toxic Chemotherapy in Locally Advanced Breast Cancer. Issue 11 (November 2020) - Carpenter, John; Forero, Andres; Falkson, Carla I.; Nabell, Lisle M.; De Los Santos, Jennifer F.; Krontiras, Helen; Bland, Kirby I.; Li, Yufeng; Bae, Sejong
Abstract : Objectives: Preoperative chemotherapy produces tumor shrinkage in most patients with locally advanced breast cancer, including some pathological complete responses (pCRs). We attempted this using a much less toxic sequential regimen, given with concurrent bevacizumab. Methods: Patients with locally advanced breast cancer received 3 intravenous doses each of preoperative sequential liposome encapsulated doxorubicin 25 mg/m 2, paclitaxel 175 mg/m 2, and cyclophosphamide 600 mg/m 2, with concurrent bevacizumab every 2 weeks without growth factor support. Results: Between March 2008 and December 2009, 32 patients received treatment. There was no cardiotoxicity, and other toxicity was mild (no grade 4 or 5 toxicity). No long-term toxicity, including cardiotoxicity, has been observed. Every patient had ≥30% reduction in tumor size; 9 of 31 patients who completed chemotherapy had pCR at operation. Seven years later, 22 of 32 patients remain free of recurrence and 27 of 32 are alive. Conclusions: The preoperative chemotherapy used appears to be comparably effective, but much less toxic than that used in most conventional regimens and should be studied further. Concurrent treatment with bevacizumab (reported separately) did not provide any additional benefit. Abstract : Preoperative sequential chemotherapy with liposomal encapsulated doxorubicin, paclitaxel, and cyclophosphamide in this pilot trial produced a pathological complete response rate of 29%, comparable to that seen with conventional anthracycline containing regimens. There was dramatically less immediate toxicity and no apparent long-term toxicity. Seven years after treatment, 22 of 32 patients remain free of recurrence and 27 of 32 remain alive.